Balancing act: when is an elite athlete who has had COVID-19 safe to return to play? When does prudent investigation go offside into overmedicalising? - Jorstad, H. T.; Aardweg van den, J. G. (British Journal of Sports Medicine, 2020)
Sport and exercise medicine (SEM) physicians are faced with the challenge of advising elite athletes with (suspected) COVID-19 wishing to return to play. Elite athletes are markedly different from the typical hospitalised patients with COVID-19. Elite athlete populations have a low prevalence of overweight and obesity, hypertension and smoking, and of lifestyle-related diseases, such as atherosclerotic coronary artery disease, congestive heart failure and obstructive lung disease, all of which are associated with severe COVID-19.However, from an athlete`s point of view, COVID-19 sequelae leading to even a small long-term decrease in physical performance capacity can be career limiting. Identifying specific symptoms, signs or findings that are associated with adverse (performance) outcomes will assist in refining management from a disease-oriented approach to a (more customised) symptom-oriented approach; the practical guide by Wilson et al is a first and important step in this direction. With a symptom-oriented approach, there is no demand for highly specialised pulmonary or cardiac expertise for SEM physicians, overmedicalisation is reduced, and the athlete`s perspective remains central.